2019
DOI: 10.1177/2156759x19878120
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Science: A Path Toward Strengthening School Counselor Practice

Abstract: Implementation science (IS) includes deliberate actions that facilitate the translation of research into practice. School counselors can use IS within the context of evidence-based practice to deliver, evaluate, and sustain programs and interventions that maximize student outcomes. This article offers an implementation framework and drivers that complement and can strengthen the application of the American School Counselor Association National Model. Case examples demonstrate the value of IS in school counselo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…This in part is because schools represent a unique environment for mental health support and intervention, with their diverse stakeholders and multifaceted mission (Kranzler & Grapin, 2018). In their review of the utility of IS for SBMH practice, Warren and Mauk (2019) concluded that IS can play a central role in maximizing school psychology’s support for positive student outcomes, by helping to address barriers such as inadequate training of school staff for mental health support, a lack of organizational structure for EBI, and insufficient planning for the implementation of interventions.…”
Section: The Present Studymentioning
confidence: 99%
“…This in part is because schools represent a unique environment for mental health support and intervention, with their diverse stakeholders and multifaceted mission (Kranzler & Grapin, 2018). In their review of the utility of IS for SBMH practice, Warren and Mauk (2019) concluded that IS can play a central role in maximizing school psychology’s support for positive student outcomes, by helping to address barriers such as inadequate training of school staff for mental health support, a lack of organizational structure for EBI, and insufficient planning for the implementation of interventions.…”
Section: The Present Studymentioning
confidence: 99%
“…School counselors can enlist school/district personnel (e.g., administration, teachers, school nurse, school health educator) and community-based professionals to provide input into selection and delivery of programs that meet school needs. Warren and Mauk (2020) offer a framework to guide the school counselor in implementing new interventions.…”
Section: School Counselor Leadership In Implementing Tier 1–3 Interventionsmentioning
confidence: 99%
“…In addition to increasing the number of evidence-based interventions, Warren and Mauk (2020) point out that school counselor scholars and practitioners would benefit from turning attention to the factors impeding or supporting the success of their interventions. The authors suggest a clear set of guidelines for applying intervention science in school counseling to ensure the schools have the systems in place to support successful implementation of evidence-based interventions and that school counselors should be sensitive to the readiness of stakeholders to change as well as, in particular, whether the evidence-based intervention meets the needs of the school or the needs of the students for which it is intended (Warren & Mauk, 2020). The evolving focus on intervention science provides school counseling educators and practitioners with guidelines for strengthening the implementation of interventions in school settings.…”
Section: Challenges and Opportunities For Ebscmentioning
confidence: 99%
“…Excitingly, our profession is actively grappling with the implications of engaging in evidence-based practices (EBP). In the past year, multiple authors (Borders, 2019;Mullen et al, 2019;Parrow et al, 2019) have explored several topics directly related to EBP in school counseling, while other authors (Savitz-Romer et al, 2019;Warren & Mauk, 2020) have written about issues ancillary to EBP such as research practice partnerships in schools and implementation science in school counseling, respectively. This special issue of Professional School Counseling provides insight into the conference proceedings of the Evidence-Based School Counseling Conference (EBSCC; http:// www.ebscc.org) and to creating an opportunity to continue discussions about ways we can ongoingly evolve our conceptualization of evidence-based school counseling EBSC.…”
mentioning
confidence: 99%